THE INFLUENCE OF MIND MAPPING TYPE COOPERATIVE LEARNING MODELS ON STUDENTS' MATHEMATICAL PROBLEM SOLVING ABILITIES - Harahap, Fitri Khairunnisa; Harahap, Tahilun; Rangkuti, Nurhamidah; Siregar, Lembang (FORUM PAEDAGOGIK, 2024)
A This study aims to determine the effect of the Mind Mapping cooperative learning model on the mathematical problem solving abilities of class VII students of MTsN 1 Tapanuli Selatan. The population in this study were all class VII MTsN 1 Tapanuli Selatan which consisted of 4 classes and the total number of students in class VII was 107 students. Sampling in this study was through Cluster Random Sampling where the sampling population did not consist of individuals, but consisted of groups that had the same characteristics (homogeneity). As a research instrument, data were used to test students' mathematical problem solving abilities in the form of an entry test on fractional material, where the questions totaled 10 questions and had been validated by lecturers and mathematics teachers. From the analysis of the score data for tests of students' mathematical problem solving abilities before using the Mind Mapping model, an average of 78.2 was obtained with a standard deviation of 5.56 and after using the Mind Mapping model an average of 82.3 was obtained with a standard deviation of 5.27 . The hypothesis used in this study uses the t test. Based on the results of data processing for the variables obtained by tests of students' mathematical problem solving abilities tcountttable (7.031 1.990847), these results prove that H0 is rejected and Ha is accepted in other words. There is an influence of the Mind Mapping Cooperative model on students' mathematical problem solving abilities in MTsN 1 Tapanuli Selatan. The effect of the Mind Mapping learning model on the Mind Mapping type cooperative model on the mathematical problem solving abilities of students at MTsN 1 Tapanuli Selatan is 42.25%